Determinants of island tourism development: The example of Dachangshan Island. (August 2016) - Yang, Jun; Ge, Yuting; Ge, Quansheng; Xi, Jianchao; Li, Xueming
Abstract: Islands possess their own patterns of spatial and temporal evolution as tourist destinations. Taking Dachangshan Island as an example, two key stages were identified: a 'landscape-oriented' period from 2002 to 2009, and a 'background' stage from 2009 to 2012. Co-existing with both periods was changing spatial and land-use patterns of expansion and intensification. Using spatial mapping techniques, it was found that tourist resources were found to be the original driving force, tourist transportation and social and economic factors were endogenous determinants of change, and tourist enterprises and source markets subject to government policies the exogenous factors. Highlights: Island tourism refers to the development of island improvement, complete facilities and functional upgrading. Taking Dachangshan Island as a representative case, we emphasize discussion on the overall island tourism effects. Paper, based on the continuous time and space expansion scales, reveals the characteristics of island tourism effects.